2017
DOI: 10.1080/14712598.2017.1341486
|View full text |Cite
|
Sign up to set email alerts
|

Is there a reason for concern or is it just hype? – A systematic literature review of the clinical consequences of switching from originator biologics to biosimilars

Abstract: While prescribing biosimilars to patients naive to a biologic treatment is a well-accepted practice, switching clinically stable patients from an originator to a biosimilar is an issue for clinicians. Well-designed clinical trials and real-world data which study the consequences of switching from an originator biologic treatment to its biosimilar alternative are limited, especially for monoclonal antibodies. Areas covered: A systematic literature review was conducted on PubMed to identify evidence of the conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
39
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 79 publications
1
39
0
3
Order By: Relevance
“…A biosimilar medicine can only be authorized if it has the same safety and efficacy profile as the reference medicine, and clinically relevant changes in treatment are not expected upon switching from the reference medicine to a biosimilar medicine (or vice versa) . Although prescribing biosimilars to biologic‐naive patients is well accepted, switching patients between reference and biosimilar medicines may be a concern for clinicians due to lack of clinical data and recommendations . Concerns surrounding switching to biosimilars include the possibility of increased immunogenicity, safety issues and even loss of efficacy …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A biosimilar medicine can only be authorized if it has the same safety and efficacy profile as the reference medicine, and clinically relevant changes in treatment are not expected upon switching from the reference medicine to a biosimilar medicine (or vice versa) . Although prescribing biosimilars to biologic‐naive patients is well accepted, switching patients between reference and biosimilar medicines may be a concern for clinicians due to lack of clinical data and recommendations . Concerns surrounding switching to biosimilars include the possibility of increased immunogenicity, safety issues and even loss of efficacy …”
mentioning
confidence: 99%
“…As authority‐approved biosimilars and their reference medicines contain essentially the same active substance, it is reasonable to assume that there will be no difference in how a patient's immune system reacts to the two medicines upon switching . Nevertheless, the risk of enhanced hypersensitivity or anaphylactic reactions remains a key concern among physicians …”
mentioning
confidence: 99%
“…Overall, the opportunity cost of not switching patients to biosimilar medicines is greater in lower income than higher income countries, as health care budgets are more limited. Current evidence suggests that a single switch of patients treated with original biologic to biosimilar products after patent expiry is not associated with increased risk of adverse reactions or loss of efficacy [30][31][32][33]. When there is clinical trial or registry based evidence about continued efficacy and nonincreased adverse event rate after switching of a biological medicine to its biosimilar alternative, expedited review with CMA is sufficient to select the most cost-effective treatment strategy.…”
Section: Health Economic Considerationsmentioning
confidence: 99%
“…Additionally, debate on immunogenicity has been fuelled by manufacturers of original biologic medicines [29]. Recently, however, several systematic reviews evaluated the clinical consequences of switching to biosimilar medicines, but none of them concluded increased risk of adverse events or efficacy loss [30][31][32][33]. These reviews, along with evidence generated from recent clinical trials indicate that significant and quantifiable economic benefits from switching patients on maintenance biologic medicines to their biosimilar alternatives under medical supervision should not be sacrificed for non-quantifiable and fairly low risks of immunogenicity.…”
Section: Considerations For Clinical Practicementioning
confidence: 99%
“…A systematic review of 58 studies, including 12 clinical trials, mostly involving infliximab or epoetins, suggested that the expected cost savings of switching outweighed the risks of harms 18. A later review of 57 studies, covering a wider range of compounds (infliximab and epoetins, but also adalimumab, etanercept, filgrastim, follicle stimulating hormone, genotropin, insulin glargine, and rituximab), reported that safety and efficacy were mostly unchanged after switching 19.…”
mentioning
confidence: 99%